A PLEA FOR INTRODUCING CONSPIRATORIAL REASONING IN ECONOMICS - Mădălina CALANCE; Andreea-Nicoleta DONICI (Management Intercultural, 2014)

(untitled)
Along with the economic globalization, economics must decode a more complex reality, to which classical answers are no longer helpful. Due to excessive abstraction and mathematical representation, the economic and social phenomena are partially analyzed and understood - after the delimitation from the political context that has driven and maintained them. We notice that, throughout history, global economic relations have always been altered by the achievement instinct or by the desire for power; that markets and natural order had been violated due to the interventionist factor which takes various forms: the state, the elites or groups animated by particular interests. That is why conspiracy theories can be starting points in analyzing our world, by underlying specific political and economic interests that govern the public decision system. This paper aims to plead for introducing conspiratorial reasoning in economics; a reasoning that rejects total hazard and the limits imposed by the study of unintended consequences of economic phenomena.